A unidirectional air waveguide basing on coupling of two self-guiding edge modes. (December 2018) - He, Liu; Gao, Yong-feng; Jiang, Zhen; Wang, Li-song; Zhou, Jun; Xu, Xiao-fang
Highlights: Here we present a line-defect waveguide frame with a 2D honeycomb magnetic-optical photonic crystal. We achieve a unidirectional air waveguide basing on coupling of two self-guiding edge modes. We quantificationally demonstrate its superior transmission characteristics. Abstract: Nonreciprocal waveguide plays the key role in optical communication devices because of the robustness of one-way transport along the edge. We present a 2D honeycomb magnetic-optical photonic crystal frame and realize a unidirectional air waveguide based on the coupling effect of two self-guiding one-way edge modes in proper the waveguide width. A great ideal nonreciprocal air waveguide with condensed-energy, strong stability, great nonreciprocity is achieved, and its transmission features of superiority over others configuration are demonstrated.